2019
DOI: 10.3389/fpls.2019.00838
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Membrane Lipid Metabolism and Molecular Mechanism in Peanut Cold Tolerance

Abstract: Early sowing has been extensively used in high-latitude areas to avoid drought stress during sowing; however, cold damage has become the key limiting factor of early sowing. To relieve cold stress, plants develop a series of physiological and biochemical changes and sophisticated molecular regulatory mechanisms. The biomembrane is the barrier that protects cells from injury as well as the primary place for sensing cold signals. Chilling tolerance is closely related to the composition, structure, and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 127 publications
1
52
0
Order By: Relevance
“…Peel browning is a main CI manifestation in refrigerated "Nanguo" pears during its shelf life, affecting the quality and reducing the commercial value of the pears 4 . The biomembrane is not only a barrier that protects cells from injury but also a primary location for sensing cold signals 10 . An increasing number of studies have reported that one of the main causes of CI is changes in membrane lipid composition, structure, and metabolic processes, which ultimately result in the degradation of cell membrane lipids 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peel browning is a main CI manifestation in refrigerated "Nanguo" pears during its shelf life, affecting the quality and reducing the commercial value of the pears 4 . The biomembrane is not only a barrier that protects cells from injury but also a primary location for sensing cold signals 10 . An increasing number of studies have reported that one of the main causes of CI is changes in membrane lipid composition, structure, and metabolic processes, which ultimately result in the degradation of cell membrane lipids 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The biomembrane is not only a barrier that protects cells from injury but also a primary location for sensing cold signals 10 . An increasing number of studies have reported that one of the main causes of CI is changes in membrane lipid composition, structure, and metabolic processes, which ultimately result in the degradation of cell membrane lipids 10 . In bell pepper samples, the level of total membrane lipids declined notably because of CI 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing polyunsaturated fatty acid composition in seeds has been demonstrated to contribute in conferring cold or chilling tolerance in plants, particularly during seed germination. Scientific evidence that supports this contention can be found in literature on cold tolerance research on Arabidopsis thaliana, tobacco, corn, soybean, and peanuts [28,49,52,56,61]. In cotton, cold germination studies have been carried out as early as the 1960s, although the functional roles of fatty acid composition on the ability of cotton to germinate under low temperatures has not been fully explored [62,63].…”
Section: Unsaturation Of Membrane and Storage Lipids As Breeding Targmentioning
confidence: 99%